Autonomy and trust in bioethics - O'Neill, Onora, 1941- (Gifford lectures, 2002)
In this important book, Onora O'Neill suggests that the conceptions of individual autonomy so widely relied on in bioethics are philosophically and ethically inadequate, and that they undermine rather than support relations of trust. Her book will appeal to a wide range of readers in ethics, bioethics and related disciplines.